An E-Learning and E-Training Adoptability in Iraq for Employment (International Journal of Engineering and Computer Science, 2025)
The adoption of e-training in Iraq for employment purposes has become a topic of increasing importance as the country seeks to adapt to the rapidly changing technological landscape and address the challenges of a growing workforce. This research paper investigates the adoptability of e-training in Iraq for employment purposes. It examines the key challenges and obstacles that have hindered the successful implementation of e-training and e-learning platforms in Iraqi universities. The paper reviews existing literature on the use of information and communication technologies in Iraqi higher education institutions and the barriers to e-learning adoption. The study used Al-Furat Al-Awsat Technical University (ATU) as a case study to investigate the requirements and feasibility of implementing an e-learning and e-training approach. The findings suggest that the main obstacles include a lack of awareness and understanding of the importance of e-training and e-learning, inadequate infrastructure and resources, and resistance to change from traditional teaching methods. The research paper concludes by providing recommendations to overcome these challenges and facilitate the widespread adoption of e-learning and e-training in Iraq to enhance employment opportunities.